Retraction notice to "Preparation and characterization of hydrophilic debranched starch modified by pullulanase on swollen granule starch" Food Research International, Volume 67, January 2015, Pages 212–218. (April 2017) - Hong, Yan; Liu, Guodong; Gu, Zhengbiao
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy ). This article has been retracted at the request of the Editor in Chief and authors, as it was published using the key ideas, novel experimental approaches, and conclusions of Yong-Cheng Shi of Kansas State University without attribution or acknowledgement of his contribution to the research. In addition, part of the content is covered by a signed confidentiality agreement. The Publisher regrets any inconvenience caused to the readers.